Loving justice : legal emotions in William Blackstone's England - Temple, Kathryn, 1955- (New York University Press, 2019)
William Blackstone's masterpiece, 'Commentaries on the Laws of England' (1765-1769), famously took the "ungodly jumble" of English law and transformed it into an elegant and easily transportable four-volume summary. Soon after publication, the work became an international monument not only to English law, but to universal English concepts of justice and what Blackstone called "the immutable laws of good and evil." Most legal historians regard the 'Commentaries' as a brilliant application of Enlightenment reasoning to English legal history. 'Loving Justice' contends that Blackstone's work extends beyond making sense of English law to invoke emotions such as desire, disgust, sadness, embarrassment, terror, tenderness, and happiness. By enlisting an affective aesthetics to represent English law as just, Blackstone created an evocative poetics of justice whose influence persists across the Western world. In doing so, he encouraged readers to feel as much as reason their way to justice. Ultimately, Temple argues that the 'Commentaries' offers a complex map of our affective relationship to juridical culture, one that illuminates both individual and communal understandings of our search for justice, and is crucial for understanding both justice and injustice today
Keywords: Blackstone, William, -- 1723-1780. -- Commentaries on the laws of England.; Blackstone, William, -- 1723-1780 -- Criticism and interpretation.; Blackstone, William, -- 1723-1780; Commentaries on the laws of England (Blackstone, William); Justice in literature.; Emotions in literature.; Law -- England -- History.; Practice of law -- England -- Psychological aspects.; Law -- Psychological aspects.; Law and aesthetics.; Justice dans la littérature.; Droit -- Angleterre -- Histoire.; Droit -- Pratique -- Angleterre -- Aspect psychologique.; Droit -- Aspect psychologique.; Droit et esthétique.; LAW -- Administrative Law & Regulatory Practice.; Emotions in literature; Justice in literature; Law; Law and aesthetics; Law -- Psychological aspects; Practice of law -- Psychological aspects; England; Commentaries on the Laws of England.; English legal history.; Guantanamo Bay.; Harper Lee.; Law and Humanities.; Nathaniel Hawes.; Onslow v. Horne.; Terry Lee Morris.; Westminster Hall.; Wollstonecraft.; aesthetics.; affective aesthetics.; bodies.; close reading.; commodification.; cruel optimism.; curatorial reading.; electric shock.; empathy.; empire.; excessive subjectivity.; gothic.; gradualism.; graveyard poets.; harmonic justice.; history of emotions.; jury trial.; marriage law.; orientalism.; peine forte et dure.; poetics.; poetry.; productive melancholia.; real property.; sympathy.; Criticism, interpretation, etc.; History